2014
DOI: 10.3109/0886022x.2014.916578
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathogenesis of IgA nephropathy: do toll like receptor 9-B cell activation factor-IgA class switching recombination signaling axis induce IgA hyper-production?

Abstract: IgA nephropathy (IgAN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…BAFF has been recognized as a biomarker that is associated with clinical and histopathological features [43] . In our previous studies, we revealed that high levels of BAFF can promote IgA CSR and the secretion of aberrantly glycosylated IgA1 [20,26,44] . TLR3-BAFF axis, first mentioned in the field rheumatoid arthritis, has supported in vivo that TLR3-BAFF can induce AID expression and Ig class-switching in B cells [45,46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAFF has been recognized as a biomarker that is associated with clinical and histopathological features [43] . In our previous studies, we revealed that high levels of BAFF can promote IgA CSR and the secretion of aberrantly glycosylated IgA1 [20,26,44] . TLR3-BAFF axis, first mentioned in the field rheumatoid arthritis, has supported in vivo that TLR3-BAFF can induce AID expression and Ig class-switching in B cells [45,46] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we focused on the role of IgA CSR in the pathogenesis of IgAN and hold the opinion that TLR9-BAFF pathway-induced IgA CSR may be of great significance for pathogenesis of IgAN elucidates and IgAN treatment [20] . IgA is the predominant immunoglobulin (Ig) isotype in mucosal secretions and serves as a first line of defense in the mucosa by inhibiting pathogen adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the abovementioned T-cell-depended IgA class switching, the T-cell-independent manners of IgA switching may be involved in the intensive production of IgA and Gd-IgA1 in IgAN patients. This kind of IgA switching is mediated through molecules such as tumor necrosis factor ligand superfamily members 13 [59] and 13b [60, 61] (called April and BAFF, respectively) which are important for B cell development. Authors found out that serum levels of April and BAFF were increased in IgAN patients [59, 60].…”
Section: Elevated Synthesis Of Gd-iga1—the Role Of Th2 Th17 and Tfh-mentioning
confidence: 99%
“…Aberrant APRIL expression in tonsillar germinal centers correlated with greater proteinuria and responded well to tonsillectomy with decreases in serum levels of galactose-deficient IgA1 in patients with IgAN (8). It was hypothesized that in patients with IgAN, a TLR 9-BAFF (B cell activation factor)-IgA axis may exist that can enhance IgA production (9). It was suggested that overexpression of TLR 9 mRNA and protein in PBMCs and elevated levels of serum BAFF maybe associated with overexpression of serum IgA1 and could have a role in the development of IgAN (10).…”
Section: Discussionmentioning
confidence: 99%
“…TLR activation may enhance the synthesis of IgA and alter IgA glycosylation. Upregulation of TLRs has been reported in peripheral-blood mononuclear cells (PBMCs) of patients with IgAN (8,9,10). However, TLR renal expression was not systematically studied in IgAN (11).…”
Section: Introductionmentioning
confidence: 99%